Screwworm - a new menace for Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A newly-introduced pest poses a serious Ask for Africa's domestic and wild animals and also to the human population. It is the New World Screwworm fly (NWS ), Cochliomyia hominivorax, or 'devourer of man''. Female screwworm flies lay their eggs in...